2018
DOI: 10.1080/02699052.2018.1469041
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and behavioural difficulties following severe TBI in adolescence: a comparison with a sample of peers with brain lesions of other origin and with a control group

Abstract: Adolescents with TBI are exposed at a very high risk to develop behavioural and psychological disturbances with the potential to severely affect their social re-entry. Further knowledge is needed to plan early and well-timed interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In a number of studies, TBI severity is associated with post-traumatic behavioral changes. Ratings completed by parents and/or children indicated greater internalizing and/or externalizing symptoms after moderate to severe TBI than in children with orthopedic injuries (OI) (5,12) or healthy children (13). Some studies identified greater problems following severe TBI than complicated/mild, moderate, and/or mild TBI for conduct, affective, anxiety, and ADHD problems (5,6,12), externalizing problems (14)(15)(16)(17)(18), and total behavior problems (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of studies, TBI severity is associated with post-traumatic behavioral changes. Ratings completed by parents and/or children indicated greater internalizing and/or externalizing symptoms after moderate to severe TBI than in children with orthopedic injuries (OI) (5,12) or healthy children (13). Some studies identified greater problems following severe TBI than complicated/mild, moderate, and/or mild TBI for conduct, affective, anxiety, and ADHD problems (5,6,12), externalizing problems (14)(15)(16)(17)(18), and total behavior problems (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…There is some preliminary evidence suggesting that psychological outcomes may differ according to etiology of ABI (Pastore et al, 2014;Pastore et al, 2018), although very few studies have specifically compared the outcomes of children with different causes of ABI (Pastore et al, 2013;Poggi et al, 2005). Most studies have focused on specific etiology groups to avoid the potentially confounding issue of different mechanisms of injury and pre-injury risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Impulsivity, attentional problems, reactive aggression and issues with behavioural or emotional regulation are common problems following TBI (Pastore et al, 2018;Williams et al, 2018). In cases of severe TBI, theory of mind (ToM) is often a ected (the ability to put oneself 'in another's shoes', and understand how others may think, feel and act in a manner di erent from our own experiences) (Hoskinson et al, 2019).…”
Section: Poverty and Educationmentioning
confidence: 99%